Outcome after Intraoperative Ejection of Descemet Membrane Endothelial Keratoplasty Graft: A Case Report - Kishan S. Sood; Kevin K. Ma; Charles Q. Yu (Case Reports in Ophthalmology)
Introduction: There is no data on management of intraoperative ejection of a Descemet membrane endothelial keratoplasty (DMEK) graft. We report a case of graft survival after intraoperative ejection with long-term endothelial cell counts and vision. Case Presentation: A 64-year-old woman with Fuchs corneal dystrophy underwent DMEK in the right eye, during which the graft was completed ejected from the eye, and then recovered and reinjected successfully. She subsequently also underwent DMEK in the left eye without complication. The patient had recovery of vision in both eyes to 20/20 shortly after each surgery. There was much greater loss of endothelial cells in the eye which experienced graft ejection than the eye with routine DMEK surgery (79% vs 44%). Conclusions: Our results support attempt to recover ejected DMEK graft if conditions are appropriate, but also show that there will be increased loss of endothelial cells as compared to routine surgery.